A model of Europeanisation with and without convergence - Phedon Nicolaides (Intereconomics, 2010)
There is a general consensus that member state interaction within the EU system will lead to convergence and an overall improvement of domestic policies and administrative systems. This article poses that non-convergence is also possible and develops a model of Europeanisation that explains both convergence and non-convergence. It also identifies the circumstances under which member states could spread negative policies to other member states, leading to convergence to the bottom.
Keywords: 330